Value Chain and Business Development Strategy of MOCAF Cap Kujang in Sumedang Regency - Mira Ismiyanti Pribadi; Wawan Gunawan; Rijanti Rahaju Maulani (School of Life Sciences and Technology, Institut Teknologi Bandung, 2022)
MOCAF Cap Kujang is one of the MOCAF (Modified Cassava Flour) produced in Sumedang that has been produced since 2012, but until now, the business development is still limited. The challenges in MOCAF Cap Kujang are the limited availability of raw materials, the lack of intensive marketing, and the government has not paid attention to the MOCAF business in Sumedang. This study aims to analyze value chain activities in MOCAF Cap Kujang, identify internal and external factors that influence the MOCAF Cap Kujang business, and determine the business development strategy for the MOCAF Cap Kujang business. The method used for value chain analysis was Porter's model and Hayami Method. Internal factor analysis was carried out using IFE, and external factors using EFE. The results of IFE and EFE were used to formulate strategies on the SWOT matrix. The resulting strategy was then prioritized using the AHP method. The study's results showed that value chain activities in the MOCAF Cap Kujang business consist of primary activities and supporting activities that generate added value at MOCAF by Rp1000/kg (33.33%). The main strength is the clean white of MOCAF Cap Kujang, and the main weakness is that MOCAF Cap Kujang's price is higher than other MOCAFs. The main opportunity of MOCAF Cap Kujang is that MOCAF can be a substitute for wheat for people who cannot consume gluten and the main threat is the lower price of wheat flour. MOCAF Cap Kujang's business development strategy prioritizes cooperation with various parties.